A mediação como fundamento da educação física escolar: possibilidades e limitações para a práxis educativa - Santos Filho, Otoniel Rodrigues dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Characterized as a theoretical study, having as theoretical and methodological framework the historical-dialectical materialism, the main goal of this work was to analyze and discuss the possibilities and limitations of using the Methodology of Dialectical Mediation (MDM) in Physical Education classes. This methodological proposal was created by Arnoni (2007, 2012, 2014) and has its foundations in the Dialectical Method, dialectical Logic and Ontology of the social being, qualifying itself as an alternative for teachers to work in the perspective of human emancipation, beyond political emancipation (citizenship). In this sense, the main approaches of Physical Education were exposed and analyzed, pointing in which extent the MDM fits in the pedagogical context of Physical Education and how it can overcome such approaches. Having the methodology above being exposed, it was also conducted a review of the production of knowledge in different historical moments and its relationship with the school and Physical Education nowadays. It was stated that the Methodology of Dialectical Mediation arises as a possibility to Physical Education teachers from the perspective of human emancipation, nevertheless, in order to become a reality and possibly articulated, it is still necessary for the field to study and define the knowledge and concepts it deals, comprehending their origins, nature and social function

Caracterizado como um trabalho de cunho teórico, tendo como referencial teóricometodológico o materialismo histórico-dialético, o presente estudo teve como objetivo principal analisar e discutir as possibilidades e limitações de utilização da Metodologia da Mediação Dialética (MMD) nas aulas de Educação Física. A referida proposta metodológica foi criada por Arnoni (2007, 2012, 2014) e tem seus fundamentos no Método dialético, na Lógica dialética e na Ontologia do ser social, qualificando-se como uma alternativa aos professores para trabalharem na perspectiva da emancipação humana, para além da emancipação política (cidadania). Para isso, foram expostas e analisadas as principais abordagens da Educação Física, apontando em que medida a MMD cabe no âmbito pedagógico da Educação Física e de que forma ela pode superar tais abordagens. Apresentada a referida metodologia, foi feita também uma revisão acerca da produção do conhecimento em diversos momentos históricos e de sua relação com a escola, e a Educação Física na atualidade. Constatou-se que a Metodologia da Mediação Dialética se coloca como possibilidade aos professores de Educação Física na perspectiva da emancipação humana, porém, para que se torne uma realidade e possa ser articulada, ainda se faz necessário para a área estudar e definir os conhecimentos e conceitos dos quais trata, depreendendo suas origens, natureza e função social
Keywords: Educação; Ontologia; Educação física - Estudo e ensino; Mediação; Physical education and training